TERRITORIALITY IN TOURISM KAMPUNG ALLEY AS A SHARED PUBLIC SPACE - Annisa Nur Ramadhani (Jurnal Arsitektur ARCADE, 2021)
Abstract: Kampung alley is a street network that perceived as a social space due to its function for community. One problematic thing that occur in tourism kampung alley is a significant change from activities taken place in the alley that have commercial-tourism functions and open for public. This change leads to the requirement of kampung alley to have high accessibility and openness to outsider. In this term, it will change the territoriality pattern as well as its meaning for residents. Territoriality is one kind of environmental behavior study about spatial usage of built environment. Territoriality has strong engagement with cultural and social context. This paper analyze that there are some changes and ambiguity of territoriality in the context of tourism kampung. Some personal and private activities have occur in the alley that are considered as a public space. This additional personal space is due to the lack of housing unit space. Strong bind of neighborhood connection is also taking a role so the residents can freely use alley for their personal need.Abstrak: Gang kampung merupakan jaringan jalan yang dipersepsikan sebagai ruang sosial oleh masyarakat yang tinggal di dalamnya. Salah satu permasalahan yang terjadi pada gang kampung wisata adalah adanya perubahan aktifitas yang signifikan dan memiliki fungsi komersial sebagai area pariwisata yang terbuka untuk umum. Perubahan ini menyebabkan gang kampung harus memiliki keterbukaan dan aksesibilitas tinggi terhadap pihak luar. Hal ini akan mengubah pola teritorialitas serta makna gang kampung bagi warganya. Teritori adalah salah satu jenis kajian perilaku lingkungan tentang pemanfaatan ruang lingkungan binaan. Teritori memiliki keterikatan yang kuat dengan konteks budaya dan sosial. Makalah ini menganalisis terdapat beberapa perubahan dan ambiguitas teritori dalam konteks kampung pariwisata. Beberapa aktivitas pribadi dan privat dapat terjadi di gang yang dianggap sebagai ruang publik. Tambahan personal space ini disebabkan keterbatasan ruang rumah kampung. Ikatan yang kuat antar tetangga juga turut berperan agar warga bisa leluasa menggunakan gang untuk kebutuhan pribadinya.